Analisis Kinerja Perusahaan CV. Bali Indah dengan Metode Balanced Scorecard - PS. Saraswati; DP. Darmawan; K Suamba (Universitas Udayana, 2017)
ABSTRACTANALYSIS OF COMPANY PERFORMANCE OF CV. BALI INDAHWITH BALANCED SCORECARD METHODBusiness competition has raised the work standard in various dimensions suchas quality, cost, and smooth operation. The challenge caused by the increasingcompetition is that companies or institutions will do anything that is consideredimportant for strategic competitiveness and overall business improvement. That is,companies will always compete to attract customers by offering various facilities atcompetitive prices. This situation will obviously encourage the management to makecertain strategies in order to win the competition and achieve companies ultimategoals. This study entitled